IMPLEMENTATION OF SKETCHBOOK APPLICATIONS IN THE CREATION OF DIGITAL POSTERS AS AN EFFORT TO INCREASE THE CREATIVITY OF PRIMARY SCHOOL TEACHERS IN SD NEGERI BAROS MANDIRI 1 CIMAHI - Rachmawanti, Ranti; Hidayat, Syarip; Yuningsih, Cucu Retno (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2023)
This globalizing technological advancement has a profound influence on all aspects of the lives of students, who must basically follow the technological developments of the millennium era in all areas of learning. One aspect affected by the effects of technological development is the aspects of art and culture. This technology enters all the fields of art, one of which is visual art. The use of communication and information media technologies as a medium source of ideas for the creation of artwork is a characteristic of new forms in art. This condition indicates that there is a need for innovation in the field of art learning, especially in elementary schools. Therefore, the community service activities are carried out by providing a form of training poster design using digital applications provided on various gadget platforms, including the Sketchbook app. This activity aims to develop and enhance the creativity of art teachers in primary schools. The target partner of this activity is SDN Baros Mandiri 1 Cimahi. Based on the results of the work already collected by the team, it can be seen that the participants actually applied the material given well into the poster that had been completed by the teachers.